Comparative proteomic analysis of unfermented cocoa beans reveals key metabolic differences between fine-flavor and bulk genotypes - de Oliveira, Ana Caroline; Vertommen, Didier; Pyr dit Ruys, Sébastien; Rogez, Herve; Debode, Frédéric; Mingeot, Dominique; Bertin, Pierre; Muhovski, Yordan (Frontiers in Plant Science, 2025)
The organoleptic quality of cocoa beans is influenced by both post-harvest processing and genotype. Fine-flavor cocoa genotypes are especially valued for their distinctive sensory attributes, yet the proteomic differences underlying these traits remain poorly understood. In this study, we conducted a comparative proteomic analysis of unfermented beans from four Theobroma cacao genotypes with contrasting flavor profiles: CCN51, EET19, P7, and PA121. A total of 2,015 proteins were identified, of which 198 proteins showing significantly different abundance relative to the fine-flavor genotype EET19. Principal component analysis (PCA) effectively distinguished genotypes based on their proteomic profiles. Notably, storage proteins were more abundant in the fine-flavor genotypes, while enzymes associated with flavor precursor formation were differentially expressed. These findings provide novel insights into the proteomic basis of flavor potential in cocoa, offering targets for genotype selection and quality improvement.